Essential Microsoft Operations Manager - Fox, Chris (O'Reilly, 2006)
For system administrators, ensuring that all Windows servers are performing optimally is a tall order. The larger the enterprise, the greater the chance for irritating, time-consuming configuration problems. Sometimes, you can determine the root cause of the problem yourself-but that's only if you're lucky. With Microsoft Operations Manager (MOM), the diagnosis is done for you. MOM monitors server operations and automatically notifies you of problems by sending an immediate alert to your console, email address, or pager. To help you better understand how MOM works, O'Reilly presents Essential Microsoft Operations Manager . The goal of this comprehensive tutorial is to give first-time MOM administrators a solid foundation for planning, implementing, and administering MOM 2005. Author Chris Fox, a renowned MOM expert, offers the type of practical, real-world advice that you need to improve the performance of your IT infrastructure. After taking you through the entire process of setting up MOM on the network, the book moves on to more advanced administration issues. It carefully instructs you how to program and automate MOM and the agents that reside on the servers themselves. You'll also learn how to manage the scripts that determine which server agents are relevant to report. By capturing system data, intelligently analyzing it, and then notifying you with a suggested course of action, MOM makes extinguishing fires a breeze. And now, thanks to Essential Microsoft Operations Manager , learning how to use MOM is a breeze, too.